2020
DOI: 10.36998/jkmm.v8i2.84
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Derajat Keparahan Akne Vulgaris dengan Kualitas Hidup menggunakan Dermatology Life Quality Index (DLQI)

Abstract: Background: Quality of life is an individual's perception of his life in the context of culture and values ​​in a place of residence with the relationship of goals, expectations, standards and concerns. Acne is a problem that can have an impact on a person's quality of life because of the shame felt by sufferers. Purpose : To describe the relationship between severity degree of acne vulgaris with quality of life using the Dermatology Life Quality Index assessment. Methods : This research is an analytical obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…These results are in line with those found by Alfein (2022) at SMA Insan Kamil Bogor, where it was found that the greater the severity of AV, the more severe the impact on the participant's quality of life (p = 0.000, r = 0.524). Research conducted by ( 2021) at FKIK UIN Maulana Malik Ibrahim Malang found a positive correlation between the severity of acne vulgaris and the quality of life of students.…”
Section: The Relationship Between the Severity Of Acne Vulgaris And T...supporting
confidence: 91%
See 2 more Smart Citations
“…These results are in line with those found by Alfein (2022) at SMA Insan Kamil Bogor, where it was found that the greater the severity of AV, the more severe the impact on the participant's quality of life (p = 0.000, r = 0.524). Research conducted by ( 2021) at FKIK UIN Maulana Malik Ibrahim Malang found a positive correlation between the severity of acne vulgaris and the quality of life of students.…”
Section: The Relationship Between the Severity Of Acne Vulgaris And T...supporting
confidence: 91%
“…The minority is in the severe impairment category (10.5%). Research carried out by Alfein (2022) at Insan Kamil Bogor High School found that the majority of respondents were only affected by mild disorders, amounting to 27 people, amounting to 49.1%, moderate disorders amounting to 14 people, 25.5%, and those experiencing severe disorders were 12 people, totaling 21.8 %. 2 people were not disturbed, amounting to 3.6%.…”
Section: Quality Of Student Lifementioning
confidence: 99%
See 1 more Smart Citation